A city‐scale assessment reveals that native forest types and overstory species dominate New York City forests. Issue 1 (6th December 2018) - Pregitzer, Clara C.; Charlop‐Powers, Sarah; Bibbo, Silvia; Forgione, Helen M.; Gunther, Bram; Hallett, Richard A.; Bradford, Mark A.
Abstract: Cities are increasingly focused on expanding tree canopy cover as a means to improve the urban environment by, for example, reducing heat island effects, promoting better air quality, and protecting local habitat. The majority of efforts to expand canopy cover focus on planting street trees or on planting native tree species and removing nonnatives in natural areas through reforestation. Yet many urban canopy assessments conducted at the city‐scale reveal co‐dominance by nonnative trees, fueling debates about the value of urban forests and native‐specific management targets. In contrast, assessments within cities at site or park scales find that some urban forest stands harbor predominantly native biodiversity. To resolve this apparent dichotomy in findings, about the extent to which urban forests are native dominated, between the city‐scale canopy and site‐level assessments, we measure forest structure and composition in 1, 124 plots across 53 parks in New York City's 2, 497 ha of natural area forest. That is, we assess urban forests at the city‐scale and deliberately omit sampling trees existing outside of forest stands but which are enumerated in citywide canopy assessments. We find that on average forest stand canopy is comprised of 82% native species in New York City forests, suggesting that conclusions that the urban canopy is co‐dominated by nonnatives likely results from predominantly sampling street trees in prior city‐scale assessments. However, native tree species' proportion declines to 75% and 53% in the midstory and understory, respectively, suggesting potential threats to the future native dominance of urban forest canopies. Furthermore, we find that out of 57 unique forest types in New York City, the majority of stands (81%) are a native type. We find that stand structure in urban forest stands is more similar to rural forests in New York State than to stand structure reported for prior assessments of the urban canopy at the city scale. Our results suggest the need to measure urban forest stands apart from the entire urban canopy. Doing so will ensure that city‐scale assessments return data that align with conservation policy and management strategies that focus on maintaining and growing native urban forests rather than individual trees.